Calibrating and Profiling the Dry Toner Based Digital Printing Machines Using Suitable Colour Management Systems “Case Study of Avantika Printers Private Limited, New Delhi” - Shama, Bijender, Ankit Boora (International Journal of Advanced Science and Technology, 2020)
The project work is carried out at Avantika Printers Private Ltd., New Delhi.The Canon ImagePRESS C8000VP dry toner based digital printing machine is taken into consideration for calibration and profiling work under standard press room conditions. A Magno matt paper is used as a substrate.The facilities of Curve4 Software are explored to make calibration and profiling of the digital press.The P2P51 test chart is used for colour space matching purposes.The i1i SIS scanning systems are used for colour measuring, calibration and profiling work. The profiles generated in this project work are recorded for further use which helps in future calibration. This project work will help in managing the colour as per pre decided specifications using advanced colour management software i.e. Curve4 software and also matching the colour space of printed samples with pre decided specifications.